A phytoestrogen secoisolariciresinol diglucoside induces browning of white adipose tissue and activates non-shivering thermogenesis through AMPK pathway. (August 2020) - Kang, JongWook; Park, Jinbong; Park, Woo Yong; Jiao, Wenjun; Lee, Sujin; Jung, Yunu; Youn, Dong-Hyun; Song, Gahee; Cho, Seon Yeon; Kim, Whi Young; Park, Ja Yeon; Ahn, Kwang Seok; et al.
Graphical abstract: Abstract: Secoisolariciresinol diglucoside (SDG) is the main phytoestrogen component of flaxseed known as an antioxidant. Current study focused on the effect of SDG in white adipose tissue (WAT) browning. Browning of WAT is considered as a promising treatment strategy for metabolic diseases. To demonstrate the effect of SDG as an inducer of browning, brown adipocyte markers were investigated in inguinal WAT (iWAT) of high fat diet-fed obese mice and genetically obese db/db mice after SDG administration. SDG increased thermogenic factors such as uncoupling protein 1, peroxisome proliferator-activated receptor gamma coactivator 1 alpha and PR domain containing 16 in iWAT and brown adipose tissue (BAT) of mice. Similar results were shown in beige-induced 3T3-L1 adipocytes and primary cultured brown adipocytes. Furthermore, SDG increased factors of mitochondrial biogenesis and activation. We also observed SDG-induced alteration of AMP-activated protein kinase α (AMPKα). As AMPKα is closely related in the regulation of adipogenesis and thermogenesis, we then evaluated the effect of SDG in AMPKα-inhibited conditions. Genetic or chemical inhibition of AMPKα demonstrated that the role of SDG on browning and thermogenesis was dependent on AMPKα signaling. In conclusion, our data suggest SDG as a potential candidate for improvement of obesity and other metabolic disorders.